Mobile Ocean Bottom Seismometer Instrument (MOBSI) data from Arctic rivers, lakes, and seas ... - Angelopoulos, Michael; Ryberg, Trond; Rasmussen, Christian; Haberland, Christian; Juhls, Bennet; Dallimore, Scott; Boike, Julia; Overduin, Pier Paul (Zenodo, 2023)
We collected the data using the Mobile Ocean Bottom Seismic Instrument (MOBSI). The MOBSI is portable (9 kg) and consists of a watertight, heavy-duty pressure housing (diameter 30 cm, height 35 cm) containing a three-component, broadband seismic sensor. There are three channels (two horizontal and one vertical) recorded by the built-in data logger to monitor ambient seismic noise. Deployed by a steel cable from a small boat or zodiac, the device was lowered to the bottom of the water bodies or the top of the beach area (if present). The device recorded ambient seismic noise for a few minutes before being retrieved and moved to a new location. The steel cable was outfitted with a communications cable, which allowed for live data analysis and quality control via a shipboard monitor. This ensured that the tilt of the instrument was correct (less than 5 degrees) and that the deployment time was sufficient. We stopped data collection when the "real-time" H/V ratio was stable, i.e., not changing with time. For all ...